Fur seal genotypes - Hoffman, Joseph I; Forcada, Jaume; Amos, William; Hoffman, Joseph I; Forcada, Jaume; Amos, William (Dryad Digital Repository, 2010)
Multilocus genotypes of 84 dead male Antarctic fur seals